2018
DOI: 10.1136/tobaccocontrol-2018-054625
|View full text |Cite
|
Sign up to set email alerts
|

Polytobacco use among young adult smokers: prospective association with cigarette consumption

Abstract: Background. The risks of polytobacco use among young adults are unclear because we know relatively little about the consistency of multiproduct patterns over time and how these patterns impact cigarette smoking. The purpose of this study was to examine changes in multiple tobacco product use over time and associations with cigarette smoking quantity.Methods. Participants (n=335; 55% male) were 18–24 years old non-daily cigarette smokers living in California. Polytobacco use patterns were assessed quarterly for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
(53 reference statements)
2
8
0
Order By: Relevance
“…The results of the present study are also consistent with previous research among North American young adults that reported using at least two tobacco products, with shisha being the most common, followed by regular cigarettes and e-cigarettes [37]. The tendency toward polytobacco use is worrying, since young adults who use more tobacco products are at a greater risk for increased regular cigarette smoking and also for maintaining this polytobacco pattern of use [38].…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study are also consistent with previous research among North American young adults that reported using at least two tobacco products, with shisha being the most common, followed by regular cigarettes and e-cigarettes [37]. The tendency toward polytobacco use is worrying, since young adults who use more tobacco products are at a greater risk for increased regular cigarette smoking and also for maintaining this polytobacco pattern of use [38].…”
Section: Discussionsupporting
confidence: 90%
“…Available research provides evidence that dual- and poly-tobacco use represents a significant public health problem 9 . Also, concurrent use of tobacco products is associated with increased risk of nicotine dependence and smoking-related health complications 10 . Due to changing patterns of tobacco/nicotine use, it is necessary to have data on prevalence and patterns of concurrent use of these products.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were not found for single and dual tobacco users. Therefore, as other authors have proposed, it appears that the use of more tobacco products is associated with more positive cognitions, a reduction in the perceived risk of tobacco use, and the sustained use of these products [17,26]. Moreover, for waterpipe use, more positive cognitions were found for all types of currents users (single, dual and poly users), than were reported by non-users.…”
Section: Discussionmentioning
confidence: 63%